2002
DOI: 10.1051/forest:2001007
|View full text |Cite
|
Sign up to set email alerts
|

Survival after outplanting of the ectomycorrhizal fungus Laccaria bicolor S238N inoculated on Douglas fir (Pseudotsuga menziesii (Mirb.) Franco) cuttings

Abstract: -Selected strains of ectomycorrhizal fungi can be inoculated in forest nurseries to improve survival and growth of seedlings or cuttings after field transplantation. The survival of the American strain Laccaria bicolor S238N on Douglas fir cuttings was evaluated in nursery and field conditions three years after outplanting using morphological and PCR/RFLP of nuclear rDNA spacers. The comparison of the mycorrhizal status of Douglas fir cuttings at the end of the nursery phase and two years after outplanting sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Because of the difficulty of monitoring ECM fungal species in field samples without using molecular techniques (Di Battista et al 2002), no data on the determination of each ECM fungus inoculated into the root systems of S. balangeran plants are available. Recently, ECM roots of S. selanica and S. lamellate outplanted in the filed were monitored using molecular technique (Tata et al 2010).…”
Section: Survival Ratesmentioning
confidence: 99%
“…Because of the difficulty of monitoring ECM fungal species in field samples without using molecular techniques (Di Battista et al 2002), no data on the determination of each ECM fungus inoculated into the root systems of S. balangeran plants are available. Recently, ECM roots of S. selanica and S. lamellate outplanted in the filed were monitored using molecular technique (Tata et al 2010).…”
Section: Survival Ratesmentioning
confidence: 99%
“…It has been reported that introduced inoculum may persist a couple of years and eventually become displaced by native species (Jones et al 1997). Other studies have reported introduced inoculum to persist many years after the initial planting (Selosse et al, 1998;Sawyer et al, 2001;Di Battista et al, 2002). Prior studies using American chestnut on reclaimed mine lands indicate that ECM species present on root systems may deter the colonization of species present on mine sites (Bauman, unpublished).…”
Section: Introductionmentioning
confidence: 99%
“…The results varied from positive to negative inoculation effect. Several authors tested the effect of inoculation by ECM fungi on the development of cuttings of other coniferous trees with similar variable results Parladé et al 1999;Di Battista et al 2002). Growth hormones indoleacetic acid (iAA), α-naphthalene acetic acid (NAA) and mainly indolebutyric acid (iBA) are the most frequently used rooting stimulators in autovegetative propagation of forest trees by cuttings (Spethmann 1997).…”
mentioning
confidence: 99%